Islamic Jurisprudence and Local Wisdom in the Humanitarian Protection of Rohingya Refugees by Acehnese Figures - Fahmi, Mutiara; Djawas, Mursyid; Sumardi, Dedy; Husna, Asmaul (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
The political conflict in Myanmar has resulted in a massive exodus of the Rohingya ethnic group from their country. The acceptance of Rohingya refugees in Aceh has sparked a societal dialectic due to the increasing number of refugees. The study focused on Islamic jurisprudence and local wisdom according to influential figures in Aceh in the protection of Rohingya immigrants. The empirical legal research method was deemed appropriate to analyze the conflict between the application of Islamic law in Aceh and the rejection of Rohingya refugees. The Islamic legal approach and local wisdom were important to analyze the context of Aceh's society, which is religious and highly values its customs. This study reveals that the handling of Rohingya refugees in Aceh, according to the views of ulama, academics, political leaders, and UNHCR Indonesia representatives, emphasizes Islamic values, Acehnese local traditions, and government policies. Ulama stresses the moral and religious obligation to assist refugees, following the Teurimong Jame tradition. Political leaders highlight the importance of government regulation to prevent negative social impacts, while UNHCR emphasizes the application of international refugee protection principles. Collaboration between society, the government, and International organizations is key to a humanitarian and structured approach to addressing the issue.